Hubungan Stunting dengan Tingkat Keparahan Karies Gigi pada Anak Usia 10-12 Tahun di Kecamatan Tuah Negeri Kabupaten Musi Rawas - Abubakar Lutfi; Rostika Flora; Haerawati Idris; Mohammad Zulkarnain (Jurnal Akademika Baiturrahim Jambi, 2021)
Stunting is one of the most common malnutrition conditions. Stunting conditions can cause impaired child development including developmental disorders in the oral cavity. Stunting children are more susceptible to dental caries due to changes in saliva characteristics. This study aims to analyze the relationship between stunting and the severity of dental caries in elementary school-aged children in Tuah Negeri District, Musi Rawas Regency. Methods: This study is an analytic observational study with a cross-sectional design. A sample of 70 people was taken randomly from elementary school students in Tuah Negeri District, Musi Rawas Regency. Determination of nutritional status based on anthropometric measurements (TB/U). DMFT examination was carried out by looking at decaying, filling, and missing teeth, then the severity of dental caries was categorized into low (DMFT 0 - 2.6), moderate (DMFT 2.7 - 4.4), high (DMFT > 4.5). Data were analyzed using SPSS version 20 with Chi-Square Test analysis. Result: The results of the measurement of nutritional status showed that 34 children (48.6%) were stunted. In stunting children, there are 15 children (44.12%) in the low category, 16 children (47.06%)  in the medium category, 3 children (8.82%) in the high category. The results of the bivariate analysis obtained p = 0.000. Conclussion: There is a significant relationship between stunting and the severity of dental caries in children aged 10-12 years in Tuah Negeri District, Musi Rawas Regency. It is necessary to increase efforts to promote health related to stunting and dental health through health education activities by involving the role of parents in choosing food intake and in maintaining children's dental and oral hygiene